Revision of Nearctic species of Acerocnema Becker (Diptera: Scathophagidae) - Chagnon, Marie-Eve; Sinclair, Bradley J. (Zootaxa, 2021)
The Nearctic species of the genus Acerocnema Becker are revised. Four species are recorded including two new species: A. fasciventris (Malloch), A. merga sp. nov., A. rufula (Curran) and A. vanga sp. nov. Species descriptions, diagnoses and distribution maps are presented, including images of the male terminalia. A key to the Nearctic species is provided. COI mitochondrial DNA barcode sequences were obtained for two named and one unidentified species of Acerocnema.